Child and adolescent health in northwestern Syria: Findings from Healthy-Syria 2017 study - Abdullah Sulieman Terkawi (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
Objectives: Since the uprising in 2011, there has been limited health-care data from inside Syria in the academic literature. This study aims to provide an updated account of pediatric health needs in the northwestern part of Syria; this should help inform the management and delivery of health-care services in this population.Methods: This is a prospective study, using a data registry, of all pediatric patients seen in a single center in northwestern Syria, between February and December 2017. We used international classification of diseases (ICD-10) codes to define cases, and tested several covariates, including age, sex, season of the year, and conditions of living for possible correlations with major illness categories.Results: We included 11,819 patients, of whom 5,288 (45%) were male and 6,531 (55%) were female. Collectively, these patients had 23,427 encounters. Respiratory diseases were the most encountered illnesses among all age groups (6320 [27%]), except late teen females, among whom gynecological/obstetric complaints dominated. Infectious diseases caused the greatest disease burden across all age groups, with upper respiratory tract infections (URTIs), infectious diarrhea, and otitis media representing almost half (47%) of all cases in this category. Nutritional deficiencies were diagnosed in 978 patients (8%), mostly in infants and toddlers (92%). We identified 1192 (17%) cases of acute diarrhea among all age groups, making it the second most common condition after URTIs. As compared to town residents, patients living in camps for internally displaced people accounted for more cases of infectious diarrhea (58%), chronic anemia (60%), and malnutrition (66%), especially severe acute malnutrition (76% of malnutrition cases). Vaccine-preventable illnesses represented a sizable category; we reported 69 cases of hepatitis A, 2 of poliomyelitis, 9 of pertussis, 37 of varicella, 11 of mumps, 8 of rubella, and 1 case of measles.Conclusion: We have identified urgent health-care issues in this population, including extreme malnutrition, high rates of infectious diseases, and high rates of teenage pregnancy. Also, we observed a relapse of some vaccine-preventable illnesses, such as mumps and rubella, which are likely associated with the decline in vaccination rates.